2019
DOI: 10.1186/s12879-019-3994-3
|View full text |Cite
|
Sign up to set email alerts
|

Use of ceragenins as a potential treatment for urinary tract infections

Abstract: Background Urinary tract infections (UTIs) are one of the most common bacterial infections. High recurrence rates and the increasing antibiotic resistance among uropathogens constitute a large social and economic problem in current public health. We assumed that combination of treatment that includes the administration ceragenins (CSAs), will reinforce the effect of antimicrobial LL-37 peptide continuously produced by urinary tract epithelial cells. Such treatment might be an innovative approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 53 publications
(58 reference statements)
5
38
0
Order By: Relevance
“…Interestingly, these compounds can be useful in preventing biofilm formation by P. aeruginosa, E. coli (associated with UTI), or Streptococcus pneumoniae. 16,25,42 Additionally, the ability of CSAs to modulate mixed species biofilms formed by organisms like P. aeruginosa and S. aureus or C. albicans and S. aureus was observed. 37,43 Additionally, Durnaś et al 19, demonstrated the significant inhibition of biofilm generation by fungi as C. albicans.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Interestingly, these compounds can be useful in preventing biofilm formation by P. aeruginosa, E. coli (associated with UTI), or Streptococcus pneumoniae. 16,25,42 Additionally, the ability of CSAs to modulate mixed species biofilms formed by organisms like P. aeruginosa and S. aureus or C. albicans and S. aureus was observed. 37,43 Additionally, Durnaś et al 19, demonstrated the significant inhibition of biofilm generation by fungi as C. albicans.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, all ceragenins tested (CSA-13, CSA-44, CSA-131) have been shown to penetrate the extracellular matrix and eradicate a biofilm in a dose-dependent manner. 20,25 Importantly, even non-toxic doses of ceragenins (at least 5-10 μg/mL) inhibit the biofilm formation in the 40-50% range.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Substantial efforts have been expended in development of endogenous antimicrobial peptides (AMPs) as new therapeutic options suitable in the treatment of drug-resistant microbial infections. For example, Wnorowska et.al, 2019 reported that combination of natural peptide LL-37 with synthetic analogs might be a potential solution to treat UTIs caused by drug-resistant bacteria [318]. UTI is one of the most prevalent diseases with diverse etiological agents annually affecting 250 million and causes death of 150 million people overall.…”
Section: Recurrent Urinary Tract Infectionsmentioning
confidence: 99%